(untitled) (Human Computation, 2016)
This paper focuses on an unexplored dimension of Citizen Science: the educational potential of Volunteer Computing (VC). VC has been one of the most popular forms of Citizen Science, since its beginnings from 1997, when the first VC platforms, such as SETI@home, were created. Participation in VC is based on volunteers donating their idle computer resources to contribute to large scale scientific research. So far this has often been seen as a rather passive form of participation, compared to other online Citizen Science (or citizen cyberscience) projects, since volunteers are not involved in active data collection, data analysis or project definition. In this paper we present our research conducted in 2013-2014 with the BOINC Community “Alliance Francophone”, and demonstrate that part of the volunteers in Distributed Computing research projects are not passive at all. We show that the dynamism of BOINC hugely relies on community-led gamification and that participation may lead to important learning outcomes on most dimensions of our ILICS (Informal Learning in Citizen Science) model. This includes extending one’s scientific interests, ability to find and engage with people who share similar interests, and offering a range of potential learning outcomes, particularly within the fields of (a) computer and Internet literacy, (b) scientific knowledge and literacy, (c) communication: English and social skills. As demonstrated by our recent ILICS survey research (2015), these latest learning effects happen for all kinds of participants and are even stronger for people who have a lower education background, which is an interesting finding for lifelong education policies. Altogether, VC projects engage volunteers emotionally, far beyond a simple use of their computers’ time and power, and may have an educational value. For a minority of very active volunteers, they become real “Opportunity Spaces”, where they can get new friends, skills and experiences, which they could not have found easily elsewhere in their everyday environment.